WOMEN AND WORSHIP FROM THE PERSPECTIVES OF CHRISTIAN CHURCHES AND CANON LAW - Synek, Eva M (Journal of Dharma, 2001)
In the New Testament, (i.e. the canonical collection of scriptures deriving from the Jesus-movement), the conviction is expressed that the last days of the world have arrived, or in other words: that the Kingdom of God, His New World, has come very close, that it is already here - at least in its nucleus. As it seems, Paul expected the second arrival of the Messiah, of the Christ, and thus the definite end of-this world during his own life-time. Such apocalyptic enthusiasm was disappointed by historical progress. Only one generation after Paul, the author of the second epistle to the Thessalonians had to warn the followers of the Jesus-movement of too much distance from worldly affairs. Normal life had to go on. That did not only mean: "If anyone will not work, neither shall he eat" (2 Tessalonians 3: 1Ob). Normal life had go on.